Gonorrhoea Infection Prevalence in Human Immunodeficiency Virus Positive Patients Based on Polymerase Chain Reaction Examination - Diah Puspitosari; Asmaja Soedarwoto; Dendi Sandiono; Feilicia Henrica Teja; Rini Rasianti; Rasmia Rowawi; Rahmatdinata Rahmatdinata; Tony Djajakusumah (Faculty of Medicine Universitas Padjadjaran, 2014)
Objective: To determine the prevalence of gonorrhoea infection in male and female HIV positive patients based on polymerase chain reaction (PCR) examination at the Teratai Clinic, Dr. Hasan Sadikin General Hospital Bandung.Methods: This study was conducted in July, 2012 at the Teratai Clinic, while the PCR examination was performed at the Molecular Biology Laboratory of Microbiology Department, Faculty of Medicine, Universitas Padjadjaran, Bandung. This was a cross-sectional observational study. The subjects were 81 HIV positive patients who were taken in consecutive admission. They underwent history taking and physical examination. Samples were taken from urethral swab in males and cervical swab in females for PCR examination.Results: The PCR examination result was positive for gonorrhea in 36% subjects. From all male subjects participating in the study, 37% were positive while 33% of the female subjects were also positive for gonorrhea. Conclusions: The prevalence of gonorrhoea infection in male and female HIV positive patients at the Teratai Clinic, Dr. Hasan Sadikin General Hospital Bandung is quite high, i.e 37% and 33%, respectively.Keywords: Gonorrhoea, human immunodeficiency virus, polymerase chain reaction, prevalence DOI: 10.15850/ijihs.v2n1.270